User experiences of a smartphone-based attentive eating app and their association with diet and weight loss outcomes: Thematic and exploratory analyses from a randomized controlled trial - Whitelock, V; Kersbergen, I; Higgs, S; Aveyard, P; Halford, JC; Robinson, E (JMIR Publications, 2020)
Background: Short-term laboratory studies suggest that eating attentively can reduce food intake. However, in a recent randomized controlled trial we found no evidence that using an attentive eating smartphone app outside of the laboratory had an effect on energy intake or weight loss over 8 weeks.